Functional Database in Gateway-based Price Service System - Sucipto Sucipto; Fitra Bagoes Hariawan; Vivin Nurita; Aditya Gusti Tammam (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2018)
Information on product prices is one of the things that is often disturbed by society because information about product prices is frequently different among sellers. Whereas the government has made information disclosure in the form of a standard price of a product that aims to reduce price differences among sellers but it cannot be denied that there are several factors that make the price of products different. For example regional factors, transportation, or limited stock. When the community has obtained price information from the government, the public can compare prices on the market. However, the disclosure of information from the government regarding the standard up-to-market price of products on the market is still through internet. Internet media cannot be fully accessed by all people, especially rural communities who still have remote areas such as Gadungan village in Kediri regency. This research was conducted as an alternative technology to facilitate information disclosure of product prices. The method used in this study is action reseach. In this research phase, researchers used the gateway service technology service with a functional PostgreSQL database. The results on usability testing showed that the average score was 88.3%. Application testing results obtained from the application effectiveness level in the range of 89%, the application effectiveness level in the range of 90% and on application satisfaction in the range of 86%. The use of the application is expected to help the public in getting more varied pricing information so as to achieve perfect price competition*****Informasi harga produk menjadi salah satu hal yang sering diresahkan masyarakat karena informasi mengenai harga produk sering berbeda dikalangan penjual. Padahal pemerintah telah melakukan keterbukaan informasi berupa standar harga pokok sebuah produk. Sesungguhnya standar harga produk dari pemerintah tersebut bertujuan untuk mengurangi perbedaan harga di kalangan penjual. Walaupun tidak bisa dipungkiri terdapat beberapa faktor yang membuat harga produk berbeda-beda. Misalnya faktor wilayah, transportasi, ataupun keterbatasan stok. Ketika masyarakat telah memperoleh informasi harga dari pemerintah, masyarakat dapat melakukan perbandingan harga di pasaran. Namun keterbukaan informasi dari pemerintah terkait standar harga produk di pasaran yang up to date masih melalui media internet. Media internet tidak dapat sepenuhnya diakses oleh semua masyarakat, khususnya masyarakat desa yang masih memiliki kawasan wilayah terpencil seperti Desa Gadungan Kab. Kediri. Penelitian ini dilakukan sebagai alternatif teknologi untuk menfasilitasi keterbukaan informasi harga produk. Metode yang digunakan dalam penelitian ini adalah action research. Penelitian ini menggunakan layanan teknologi gateway service dengan fungsional database PostgreSQL. Hasil penelitian berdasarkan pengujian usability testing diketahui bahwa rata-rata score adalah 88,3%. Hasil pengujian aplikasi didapatkan dari tingkat efektivitas aplikasi pada kisaran 89%, tingkat efektivitas aplikasi pada kisaran 90% dan pada kepuasan aplikasi pada kisaran 86%. Penggunaan aplikasi diharapkan dapat membantu masyarakat dalam mendapatkan informasi harga lebih variatif sehingga mencapai persaingan harga sempurna dengan teknologi informasi menggunakan metode gateway service.